Formulation and Evaluation of Orally Disintegrating Tablet Containing Aripiprazole in the Context of Quality by Design Approach - Kalayı, Mehmet; Barbar, Arkan Yashar; Aksu, Buket (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background The objective of this research is to develop and enhance the formulation of aripiprazole rapid disintegrating tablets utilizing the Quality by Design (QbD) methodology. Materials and Methods A full factorial experimental design with three levels was employed to analyze the influence of key factors, namely the concentration of the filler (starch), ludipress concentration and disintegrant concentration, on important quality attributes such as disintegration time, friability and hardness. The formulation's drug-excipients interaction was examined using FTIR. Research was conducted to assess the stability of the product in accelerated conditions of 40ºC and 75% relative humidity. Results FTIR analysis indicated that there was no notable chemical interaction seen in the solid form. The Aripiprazole fast disintegrating tablet formulations demonstrated satisfactory friability (0.77±0.16%), rapid disintegration time (66±0.58 sec) and appropriate hardness (48.35±3.22 N). The research revealed that the most favorable combination of independent components consisted of 15.8% filler (starch), 76% ludipress and 1.3% disintegrant. Conclusion The accelerated stability experiments demonstrated that the hardness, friability, disintegration durations and drug release rate were within the permissible limits defined by the compendial standards. Implementing the Quality by Design (QbD) method may facilitate a comprehensive comprehension of how the Critical Material Attributes (CMAs) impact the Critical Quality Attributes (CQAs) of the final product of aripiprazole rapid disintegrating tablets.
Keywords: Aripiprazole; Fast disintegrating tablets; Quality by design QBD; Stability; Super-disintegrants